The Influence of the Picture and Picture Learning Model on the Science and Social Learning Outcomes of Grade IV Students of SD Negeri 134633 Tanjungbalai - Marbun, Aloisya; Panggabean, Eva Saryati; Purba, Jon Roi Tua (Lembaga Riset Mutiara Akbar, 2025)
This study aims to determine the effect of the Picture and Picture learning model on the learning outcomes of fourth-grade students of SD Negeri 134633 Tanjungbalai. The type of research used is quantitative research with an experimental method, using a One Group Pretest-Posttest design. The research sample was fourth-grade students consisting of 7 male students and 13 female students. The data collection technique was carried out by a multiple-choice test on the material of Plant Reproduction, which was used as a pretest and posttest. Scores were given with a value of 1 for correct answers and 0 for incorrect answers. The test was given before and after treatment. The data analysis technique used a normality test and hypothesis test. The results of the t-test showed that the t-count value was 18.812, while the t-table was 1.729 with a significant level (2-tailed). Because the t-count (18.812) was greater than the t-table (1.729), it can be concluded that there is a significant influence of the Picture and Picture learning model on the learning outcomes of fourth-grade students of SD Negeri 134633 Tanjungbalai. Thus, the alternative hypothesis (Ha) is accepted and the null hypothesis (H0) is rejected.